EDUCATIONAL MANAGEMENT AND TEACHING PERFORMANCE IN PUBLIC EDUCATIONAL INSTITUTIONS OF THE UGEL 03 OF METROPOLITAN LIMA - MOLERO-FARMAN, Alvaro (2024)
The present study aims to determine what relationship exists between educational management and teacher performance in public educational institutions of UGEL 03 of Metropolitan Lima. The research is quantitative, non-experimental design, correlational and cross-sectional. The population is composed of 56 teachers working in the public educational institutions of UGEL 03 and the sample, having a 95% confidence level, is composed of 50 teachers. In addition, for the educational management variable, a questionnaire consisting of 21 items was applied, measured with an ordinal Likert-type scale, presenting a high reliability because the Cronbach’s Alpha value is 0.939. Likewise, for the teacher performance variable, a questionnaire consisting of 20 items was applied, measured with an ordinal Likert-type scale, presenting a high reliability because the Cronbach’s Alpha value is 0.890. It is concluded that there is a direct and significant relationship between the two variables studied and between the dimensions of educational man agement and the teacher performance variable.